2018
DOI: 10.1101/358333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wolbachia pipientisassociated to tephritid fruit fly pests: from basic research to applications

Abstract: 23hominivorax Coquerel); several species of tsetse fly (Glossina spp.); and the codling 71 moth (Cydia pomonella L.) [reviewed in 17, 18]. 72 73 Successful SIT programs as part of Area-wide Integrated Pest Management (IPM) 74 strategies have also been implemented for several tephritids: Ceratitis capitata 75 Wiedemann; Anastrepha ludens Loew; Anastrepha obliqua Macquart; Anastrepha 76 fraterculus Wiedemann; Zeugodacus cucurbitae Coquillett; Bactrocera dorsalis Hendel; 77and Bactrocera tryoni Froggatt [6, 12, 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 247 publications
(192 reference statements)
0
7
0
Order By: Relevance
“…In general, the significant role of microbiota (Wolbachia, gut bacteria etc.) in tephritid biology and behavior is widely accepted [65,104]. However, the interaction among the different bacterial communities and the way that these interactions affect insect's biology and behavior are not completely unraveled.…”
Section: Effect Of Wolbachia On Developmental Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the significant role of microbiota (Wolbachia, gut bacteria etc.) in tephritid biology and behavior is widely accepted [65,104]. However, the interaction among the different bacterial communities and the way that these interactions affect insect's biology and behavior are not completely unraveled.…”
Section: Effect Of Wolbachia On Developmental Durationmentioning
confidence: 99%
“…The following general patterns emerged: a) Wolbachia causes high egg-to-larva mortality, b) Wolbachia causes high egg-to-adult mortality (exception: Vienna 8 GSS + wCer2) and c) Wolbachia shortens egg-to-adult developmental time, although it prolongs embryonic development (exception: Benakeio + wCer2). Recent studies by Kyritsis [65,66] on the same system (Wolbachia-medfly) reported no effects of Wolbachia infection on adult lifespan and a reduced fecundity in the case of wCer4 infection only. Even though wCer2 and wCer4 in general tended to have consistent effects on medfly, the magnitude of their effects differed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much interest has been shown on studies regarding the intracellular bacterium Wolbachia that is found in more than 40% of the terrestrial arthropod species (Werren et al , 2008; Zug & Hammerstein, 2012). The presence of Wolbachia has been associated with the induction of a variety of host reproductive phenotypes such as feminization, parthenogenesis, male killing and cytoplasmic incompatibility (CI) (for review see Werren et al , 2008; Saridaki & Bourtzis, 2010; Mateos et al , 2019). For these reasons, Wolbachia is considered a key player affecting biological and evolutionary processes as well as a tool for the control of agricultural pests and disease vectors (Werren et al , 2008; Saridaki & Bourtzis, 2010; Mateos et al , 2019).…”
Section: Genetic Relationships Among the Three Rhagoletis Speciesmentioning
confidence: 99%
“…Augustinos and colleagues (2014) pointed to the presence of additional uncharacterized Wolbachia strains on R. cerasi populations from Greece, and raised concerns about the suitability of the currently used diagnostic markers for genotyping. Considering the information mentioned earlier, along with the fact that Wolbachia cannot be cultivated in the laboratory, the presence of low-titre infections and/or multiple infections in the same individual, as well as the highly recombinant nature of the bacterial chromosome, make Wolbachia characterization in R. cerasi samples a very difficult task (Zabalou et al , 2004, 2009; Schneider et al , 2013; Mateos et al , 2019). Allelic intersection analysis provided an additional tool for the characterization of multiple Wolbachia infections in R. cerasi (Arthofer et al , 2011); however, this analysis requires a priori knowledge on the Wolbachia strains harboured by a species and can be quite laborious.…”
Section: Genetic Relationships Among the Three Rhagoletis Speciesmentioning
confidence: 99%
“…Wolbachia are maternally inherited endosymbionts of insects, that are of much interest for use in the biological control of pests, most particularly as a basis for area-wide integrated control strategies for a range of insect species [9][10][11]. Wolbachia has been used in insect control programmes in two main ways.…”
Section: Introductionmentioning
confidence: 99%